Peran Fisioterapi sebagai Pendampingan Orang Tua dalam Melakukan Active Cycle Breathing Exercise pada Asma Puskesmas Medan Selayang - Heri Saputra; Riani Baiduri Siregar; Rudi Purwana (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Active Cycle Breathing Exercise (ACBE) is an effective therapeutic method for managing asthma symptoms, particularly in improving lung function and reducing the frequency of attacks. The role of physiotherapists as parental companions in implementing ACBE is crucial, especially at Medan Selayang Community Health Center. This study aims to analyze the contribution of physiotherapists in assisting parents of children with asthma to perform ACBE correctly and consistently. A descriptive research method was used, collecting data through interviews, observations, and questionnaires administered to parents and physiotherapists. The results indicate that physiotherapist involvement not only enhances parents' understanding of ACBE techniques but also improves adherence to regular practice at home. Furthermore, there was a significant reduction in asthma symptoms among children following consistent therapy. The physiotherapists' roles include education, demonstration, supervision, and evaluation of patient progress. Through this assistance, parents gain confidence in helping their children manage asthma, leading to an overall improvement in the quality of life for both children and families. This study recommends strengthening training programs for parents and integrating ACBE into physiotherapy services at the community health center level to ensure sustainable therapy.